QUALITY OF SERVICES (QOS) NETWORK COMMUNICATION EQUIPMENT USING ELECTRICAL CABLES AT POLITEKNIK PELAYARAN SURABAYA - Agus Dwi Santoso; Fery Budi Cahyono; Bambang Bagus Harianto (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2023)
This study compares internet network communication performance using electrical and network cables. Data passed using power lines is converted using power line Communication (PLC). The quality of service results on the PLC obtained a throughput value of 1,834 Kb/s, Packet loss of 0.045, delay of 34.958, and Jitter of 41.648. Data measurement using Wireshark software, by using typhoon data to convert values, the measurement results show that the throughput value is excellent, the packet loss value is excellent, the delay value is excellent, and the jitter value is good.